Financing the small manufacturer in developing countries - Davenport, Robert Wesley (New York : McGraw-Hill, 1967)
Study on financing programs in a wide variety of countries in an effort to distill from them more practical institutional arrangements than those generally employed.
Bibliographical footnotes.
sju 22/01/2019
Loans
Keywords: Finance; Small business